Nonpyrogenic Molecular Adjuvants Based on norAbu-Muramyldipeptide and norAbu-Glucosaminyl Muramyldipeptide: Synthesis, Molecular Mechanisms of Action, and Biological Activities in Vitro and in Vivo - Effenberg, Roman; Turánek Knötigová, Pavlína; Zyka, Daniel; Čelechovská, Hana; Mašek, Josef; Bartheldyová, Eliška; Hubatka, František; Koudelka, Štěpán; Lukáč, Róbert; Kovalová, Anna; Šaman, David; Křupka, Michal; et al. (Journal of medicinal chemistry, 2017)
Fatty acyl analogues of muramyldipeptide (MDP) (abbreviated N-L18 norAbuGMDP, N-B30 norAbuGMDP, norAbuMDP-Lys(L18), norAbuMDP-Lys(B30), norAbuGMDP-Lys(L18), norAbuGMDP-Lys(B30), B30 norAbuMDP, L18 norAbuMDP) are designed and synthesized comprising the normuramyl-l-α-aminobutanoyl (norAbu) structural moiety. All new analogues show depressed pyrogenicity in both free (micellar) state and in liposomal formulations when tested in rabbits in vivo (sc and iv application). New analogues are also shown to be selective activators of NOD2 and NLRP3 (inflammasome) in vitro but not NOD1. Potencies of NOD2 and NLRP3 stimulation are found comparable with free MDP and other positive controls. Analogues are also demonstrated to be effective in stimulating cellular proliferation when the sera from mice are injected sc with individual liposome-loaded analogues, causing proliferation of bone marrow-derived GM-progenitors cells. Importantly, vaccination nanoparticles prepared from metallochelation liposomes, His-tagged antigen rOspA from Borrelia burgdorferi, and lipophilic analogue norAbuMDP-Lys(B30) as adjuvant, are shown to provoke OspA-specific antibody responses with a strong Th1-bias (dominance of IgG2a response). In contrast, the adjuvant effects of Alum or parent MDP show a strong Th2-bias (dominance of IgG1 response).
Keywords: imunizace; Lipoproteins; RAW 264.7 buňky; Borrelia burgdorferi; lymeská nemoc; antigeny povrchové; HEK293 buňky; Bacterial Outer Membrane Proteins; lipoproteiny; Lyme Disease; RAW 264.7 Cells; NLR Family, Pyrin Domain-Containing 3 Protein; myši inbrední BALB C; Bacterial Vaccines; HEK293 Cells; Mice, Inbred BALB C; Adjuvants, Immunologic; protein NLRP3; Animals; lidé; Acetylmuramyl-Alanyl-Isoglutamine; bakteriální vakcíny; ženské pohlaví; Humans; adjuvancia imunologická; zvířata; tvorba protilátek; Antigens, Surface; myši; acetylmuramyl-alanyl-isoglutamin; Antibody Formation; Mice; Female; Immunization; proteiny vnější bakteriální membrány